“Strained and Strange”: Second-Year University Students' Help-Seeking Strategies - Lynnae Venaruzzo; Negin Mirriahi; Oleksandra Poquet; Shane Dawson (Student Success, 2024)
Second-year university students often experience a disconnection with their learning and may feel unmotivated, lack confidence, and are unprepared for the higher expectations and complex concepts of their courses. Their disconnection with their learning can be addressed through deepening the social connections between other second-year students, and instructors providing encouragement to seek help in their learning when they need it. There is scant research that examines the peer-interactions between second-years and how their interactions influence their help-seeking behaviours. This article focuses on the interactions and help-seeking behaviours of 26 students from a major metropolitan Australian university in 2021. Results show that peer interaction is highly valued by students but not easily facilitated, and the relationship between students and their instructor is foundational for future help-seeking behaviours. Implications for practice are also presented.